Control of nonlinear dynamical systems using genetic algorithms - Al-Duwaish, H.N. (1997)
This paper introduces a new method for the control of nonlinear systems using genetic algorithms. The proposed method formulates the nonlinear controller design as an optimization problem and genetic algorithms are used in the optimization process. Simulation examples are included to illustrate the performance and effectiveness of the proposed method